Analysis of Performance on Circular Patch Antenna Based on Different Feeding Techniques - Hamidah Abd Hamid, Saidatul; Chin Hock, Goh; T. Ali, M. (International Journal of Engineering and Technology, 2018)
This paper presents a simulation and analysis of a circular patch antenna with different feeding techniques. The objectives of this analysis are to design the microstrip circular patch antennas using five types of feedings techniques which are stepped feed, inset feed, coaxial feed, aperture coupled feed, and proximity feed, to analyze and compares the performance of the antenna design. Performance characteristics of the antenna such as return loss S11 parameter <-10dB, directivity, gain, bandwidth, side lobe level, beam width, and voltage standing wave ratio (VSWR)Â parameters of each of the feeding methods designs are obtained and compared.Â